RETRIBUSI PARKIR DI PASAR DAN TEPI JALAN RAYA WILAYAH KABUPATEN PIDIE (ANALISIS TERHADAP QANUN KAB. PIDIE NO. 21 TAHUN 2011) - Amsanul Amri; Irma Yusnita (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2020)
This research is principled and urgent in answering the problem ofparking tariff dualism in Pidie Regency, especially parking in public places suchas markets, parks and road sides. The main problem is how to practice parkingfees, a form of parking fees based on the Qanun Kab. Pidie Number 21 of 2011,and a review of Islamic law on the practice of collecting parking fees in PidieDistrict. This type of research is qualitative and uses an empirical approach as ahallmark of field research. Based on research results, parking practices andparking fee collection in the Beureunuen and Peukan Pidie markets can beidentified from the problem of parking areas, management, officers, dualism ofparking fees, and illegal parking. There are two categories of parking managementnamely parking managed by the Pidie District Government and parking managedby the local jurisdiction village. The amount of parking fees is based on QanunKab. Pidie No. 21 of 2011 is Rp. 1,000 / motorcycle for one parking. Whereas thepractice of parking tariff dualism by quoting Rp.2,000 / motorcycle according toan analysis of Islamic law is an act contrary to the law, because it is not inaccordance with the government's decision as ulil amri which is obligatory to beobeyed. With regard to the practice of dualism of parking tariffs on the side ofhighways and markets, the researcher recommends the Pidie District Governmentand its stakeholders to implement the Qanun Kab. Pidie No. 21 of 2011 as awhole, finding smart and appropriate solutions, evaluating parking managers andofficers, and taking firm actions against those who violate the law in the field ofparking.